Secure Mutual Authentication Protocol Based on Wireless Body Area Networks - Thammarat, Chalee; Techapanupreeda, Chian (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2021)
Data sent from wireless body area networks to healthcare professionals or doctors include sensitive information which needs to be protected from unauthorized access. A mutual authentication protocol is a security feature that can prevent man-in-the-middle and spoofing attacks. A number of mutual authentication protocols based on wireless body area networks have been proposed; however, these impose high cryptographic operation costs, energy costs, and time costs, and also lack some security properties. In this research, we propose an efficient mutual authentication protocol for secure data exchange to send personal health records from a smartphone device to a doctor. The proposed protocol leads to a reduction in the cryptographic operation, energy, and time costs, and uses fewer resources than previous protocols. Although our approach utilizes a one-way hash function rather than encryption, it still provides the necessary security properties, unlike existing protocols. We also formally verify our approach using the Scyther tool and AVISPA. The results show that the proposed protocol has been verified as being resistant to attack as designed.